2017
DOI: 10.1080/14764172.2016.1262960
|View full text |Cite
|
Sign up to set email alerts
|

Laser toning for melasma: A single-centre experience with 38 970 cases

Abstract: Melasma is a common pigmentation in Asian women. Lasers have been used to lighten melasma, although with variable outcomes and complications. In Asia, laser toning is a common technique used to safely lighten melasma. However, no large studies have been performed to validate efficacy. In our study, we demonstrate that in 38 970 Asian women, at least 35 890 patients (92.1%) had noticeable to excellent improvement in their melasma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 11 publications
1
7
0
Order By: Relevance
“…Tian[24] studied the effect of laser toning in 38,970 cases. He reported 21,940 patients (56.3%) reported fair improvement; 8,690 (22.3%) had good improvement; and 1,987 (5.1%) had excellent improvement.…”
Section: Laser Toningmentioning
confidence: 99%
See 1 more Smart Citation
“…Tian[24] studied the effect of laser toning in 38,970 cases. He reported 21,940 patients (56.3%) reported fair improvement; 8,690 (22.3%) had good improvement; and 1,987 (5.1%) had excellent improvement.…”
Section: Laser Toningmentioning
confidence: 99%
“…A total of 3,273 (8.4%) patients had noticeable improvement, whereas 3,080 (7.9%) had little or no improvement. [24]…”
Section: Laser Toningmentioning
confidence: 99%
“…The application of this low‐fluence laser regularly is known as “laser toning” and is a common practice in Asia. It is effective for hyperpigmented lesions such as melasma and causes less postinflammatory hyperpigmentation . When the laser is performed over entire face, clinicians can expect the effect of lightening overall skin and obscuring the distinctive border between lesional skin and non‐lesional skin .…”
Section: Discussionmentioning
confidence: 99%
“…15 They showed that 92.1% of the patients had noticeable to excellent improvement in their melasma. 15 Gokalp H et al evaluated 34 patients with melasma and revealed 50% reduction in melasma severity with QsNd-YAG laser alone with a high recurrence rate (58.8%). 16 Also, they stated that this type of laser is inadequate for long-term remission.…”
Section: Qsnd-yag Lasermentioning
confidence: 97%
“…There was no dyspigmentation or worsening in the melasma of enrolled patients. Small They showed that 92.1% of the patients had noticeable to excellent improvement in their melasma 15. Gokalp H et al evaluated 34 patients with melasma and revealed 50% reduction in melasma severity with QsNd-YAG laser alone with a high recurrence rate (58.8%) 16.…”
mentioning
confidence: 98%